Age and Qualification as Influencer of Facet-Specific Job Satisfaction - Ghazi, Safdar Rehman (Richtmann Publishing, 2011)
The purpose of this study was to document age and qualification influence on facet-specific levels of job satisfaction as measuredby the Minnesota Satisfaction Questionnaire (MSQ). The Long Form MSQ 1967 was chosen to measure satisfaction levels of twentyjob facets. The head teachers with younger and older age, bachelor degree holders, obtained high means than head teachers with middle ageand master degree holders. Significant differences were found among different age groups for different dimensions of job. Therefore, nosignificant differences were observed for qualification. Younger and older age head teachers were significantly more satisfied with almost allthe dimensions of the job than the middle age head teachers. No significant differences were found between the head teachers with bachelordegree and the head teachers with master degree for any dimension of the job. Results based on this study provide a sufficient ground toframe the following recommendations; salary of the teachers should be increased, a large amount in annual budget should be reserved toimprove the working conditions in the schools, special attention should be given to facilitate the medium age teachers, studies onsatisfaction and age should be conducted to investigate the reason why satisfaction increases in younger and older age while decreases inmiddle age, and studies on satisfaction to investigate more predictors to job satisfaction should be conducted.